Shadowing multilingual learners - Soto, Ivannia (Corwin literacy, 2021)
"In the past 10 years -- both in California and across the nation -- teachers, researchers, and policy makers have achieved numerous changes in the field of multilingual learning. California replaced the English-Only policy of Proposition 227 with the assets-based approach of Proposition 58, and 37 states have adopted a Seal of Biliteracy program, honoring students for multilingual achievement upon graduating high school. Recently, Dual Language Immersion (DLI) teachers, principals, and district administrators have utilized ELL Shadowing as part of their programs in coordination with the California Association for Bilingual Education. With the addition of applications, DLI Shadowing, and participant-adjusted consulting services, ELL Shadowing has gained in popularity over the six years, reaching more and more readers in the last two years. This long tail, combined with new research and impact data collected by the author, solidifies the need for an updated edition of ELL Shadowing"--